Effects of a carbohydrate and a carbohydrate and casein protein beverages on recovery and perfomance of endurance cycling capacity - Cepero, M.; Rojas, F. J.; Geerlings, A.; de la Cruz, J. C.; Romero, S.; Boza, J. J. (Journal of Human Sport & Exercise, 2009)
The main aim of this study was to determine if short-term post exercise recovery, cycling performance and muscle damage were altered when consuming a carbohydrate-only beverage (CHO, 7% carbohydrate) versus a carbohydrate and casein protein beverage (CHO+P, 7% carbohydrate and 4% protein). Fifteen male cyclists (VO2peak= 63.4±9.6 ml/kg·min) performed two trials using a randomly counterbalanced, double-blind design. In each trial one liter of one of the test drinks was consumed in fasting conditions after 1 hour ride at 75% VO2peak determined by Arts and Kuipers´ regression equation .After a two hours recovery period the cyclists rode 20 km at the rider's maximum speed for this distance. The results showed no significant differences in the 20-km ride when consuming the CHO (1770±210 s) or the CHO+P drink (1819±185 s). Post-exercise creatine kinase (CK) was not significantly different between treatments. However, serum insulin concentrations were higher during recovery when CHO+P beverage was consumed. Glucagon and lactic acid levels increased more on the CHO than on the CHO+P treatment at the end of the 20 km test. Within the context of this experimental design, the CHO+P drink showed different physiological effects than the CHO drink, so that the CHO+P drink can be recommended for improving recuperation from intensive exercise. Although this was not reflected in post-recovery exercise performance in this 20 km test, a harder or longer test may be more affected by the physiological parameters.